Tromboemboli pada Kehamilan - Agnesha, Fahmi; Rahardjo, Sri (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
Thromboembolism is a rare event happen in pregnancy, that if not manage well would be a catastrophic and can cause fatal outcome. Venous thromboembolic event in pregnancy form are deep vein thrombosis and pulmonal thromboembolism. The pathophysiology of thromboembolism explained by Virchow triad that describe the factor contribute are vein stasis, vascular damages and hypercoagulable state. The diagnosis of the new onset thromboembolism can be made by ultrasound examination on proximal vein. Management of thromboembolism in pregnancy is including low molecular weight heparin and unfractioned heparin administration. These treatments can cause neuraxial anesthesia impact on pregnant patient as spinal and epidural hematoma. Thus many guidelines give recommendation for stopping heparin administration before procedure.